Exclusive vital labeling of myonuclei for studying myonuclear arrangement in mouse skeletal muscle tissue - Hastings, Robert Louis (Skelet Muscle, 2020)
BACKGROUND: The arrangement of myonuclei in skeletal muscle tissue has long been used as a biomarker for muscle health, but there is a dearth of in vivo exploration of potential effects of myonuclear organization on the function and regeneration of skeletal muscle because traditional nuclear stains are performed on postmortem tissue. Therefore, we sought a transgenic method to produce a selective and persistent myonuclear label in whole muscles of living mice. METHODS: We bred together a mouse line with skeletal muscle fiber-selective expression of Cre recombinase and a second mouse line with a Cre-inducible fluorescently tagged histone protein to generate a mouse line that produces a myonuclear label suitable for vital imaging and histology of fixed tissue. We tested the effectiveness of this vital label in three conditions known to generate abnormal myonuclear positioning. First, we injured myofibers of young mice with cardiotoxin. Second, this nuclear label was bred into a murine model of Duchenne muscular dystrophy. Finally, we examined old mice from this line that have undergone the natural aging process. Welch’s t test was used to compare wild type and transgenic mice. RESULTS: The resulting mouse line transgenically produces a vital red fluorescent label of myonuclei, which facilitates their in vivo imaging in skeletal muscle tissue. Transgenic fluorescent labeling of myonuclei has no significant effect on skeletal muscle function, as determined by twitch and tetanic force recordings. In each muscle examined, including those under damaged, dystrophic, and aged conditions, the labeled myonuclei exhibit morphology consistent with established literature, and reveal a specialized arrangement of subsynaptic myonuclei at the neuromuscular junction. CONCLUSIONS: Taken together, our results demonstrate that this mouse line provides a versatile tool to selectively visualize myonuclei within both living and fixed preparations of healthy, injured, diseased, and aged muscles.